PRACTICAL ASPECTS OF ELABORATION OF INTERNATIONAL INVESTMENT PROJECT IN EDUCATION SPHERE IN JAPAN - Iryna S. Shkura; Oleksii O. Yaloza (Êvropejsʹkij Vektor Ekonomìčnogo Rozvitku, 2022)
In Japan, one of the strongest economies in the world and home to 125 million people, proficiency in English language is associated with the huge advantages and signifies privilege since the Meiji era when English was used as a tool by Japanese elite in a technological catch-up with the West. The seven years of U.S. occupation of the country after the Second World War have also left a big impact on the Japan’s economic, political and social development. The reconstruction of Japan aided by Americans altered the perception of Japanese people, associating English language with such ideas like freedom and democracy. During the seven years of occupation the country faced a lot of political and economic changes, including liberalization, and was slowly transitioning its central industries from agriculture to light manufacturing and later to heavy manufacturing. The economy of Japan has been slowly recovering from an era of economic stagnation, it is on the path of the moderate growth. Today, it is the third strongest economy with the nominal GDP of about $5.06 trillion that is focused on advanced manufacturing and export, agriculture, fishing and tourism. Japan is very special and different from other countries; a lot of great companies and unique business practices were born there. It is also leading in high-tech innovations and manufacturing. While having a lot of opportunities for various businesses, being politically stable and safe country, its bureaucracy and the comparative difficulty of doing business for foreigners makes it a controversial but potentially rewarding choose for an investment project. In the recent years, the necessity of knowing how to communicate in English has increased significantly. The school program focuses mainly on such skills as reading and writing, and a lot of attempts to reform the system has failed. That is why parents and students are approaching private language schools to master the abilities of speaking and listening. In addition, English teaching is one of the most popular jobs for foreigners in Japan. The language school market is quite saturated, but at given circumstances it can be very rewarding. The idea of the investment project is to create a private language school that will focus on giving Japanese people the practical English skills. The project involves the creation of Gōdō Kaisha (a Japanese analogue to the LLC). This type of incorporation fits the company best, considering the size and scale of the activities. As the company is not planning to issue certificates, the need for special licensing from the state is absent. Appointing a representative director is obligatory in Japan, but GK, allows to appoint a representative director who is not a resident in Japan.